(untitled) (Siddhajyoti Interdisciplinary Journal, 2021)
This study aims at examining consumers’ awareness level towards labeling information of product in marketing practices based on an empirical study of college students in Tikapur Municipality, Kailali. This study depends on a purposive sample of 180 students whichhave been selected from management, education and humanities faculties studying in graduate level at Tikapur Multiple Campus and Birendra Vidhya Mandir Campus at Tikapur, with a structured questionnaire to measure consumer buying behavior regarding the basic labeling information of packaged products, utilizing a four-point rating scale for measurement. The overall findings communicate that the aggregate consumers’ awareness level is low towards labeling information of packaged product in marketing practices. Furthermore, awareness level of management students is high in comparison to nonmanagementstudent.Similarly,maleconsumersarefoundmoreawarethanfemale.Thisstudyexploresthestatusandlevelofconsumerawarenessforthefirsttimeinstudyareaalongwiththesuggestionstoconsumers,businessmen,consumerforum,governmentunitsandpublic policymakers to improve the current status of consumer awareness, with implications for better business strategies and more useful to consumerism.